Effect of Gd2O3 in Li2O–AlF3–CaF2–P2O5–Eu2O3 glasses for laser medium and X-rays detection material applications. (October 2022) - Sarumaha, C.S.; Rajagukguk, J.; Tongdang, J.; Chanthima, N.; Kim, H.J.; Kothan, S.; Kaewkhao, J.
Abstract: The glass formula of 20Li2 O+10AlF3 +2.5CaF2 +(66.5- x )P2 O5 + x Gd2 O3 +1Eu2 O3 (PLACEu1 Gd x ), where x  = 2, 4, 6, 8, 10 mol% have been prepared by conventional melt-quenching technique. These glasses' optical absorption, photoluminescence, decay time, and radioluminescence have been measured at room temperature. Judd-Ofelt's (J-O) analysis of PLACEu1 Gd8 has been investigated and the magnitude of parameters follows the trend as Ω2 >Ω4 >Ω6 . The important laser parameters such as radiative properties are calculated using J-O parameters and luminescence spectra. The decay time with the transition from the 5 D0 level was estimated under 274 nm and 394 nm excitation using bi-exponential fitting. CIE coordinates, CCT and intensity ratio have been calculated for glass samples. The integral scintillation efficiency of PLACEu1 Gd8 is 31% compared with BGO crystal. The PLACEu1 Gd x glasses are promising for laser medium and x-rays detection material applications. Highlights: The effect of Gd2 O3 in Li2 O–AlF3 –CaF2 –P2 O5 –Eu2 O3 glasses was investigated. The phonon energy was approximate to be 1170.36 cm −1 . The quantum efficiency of PLACEu1 Gd8 glass is 97%. The light yield of the prepared glass was estimated to be 31% of the commercial BGO crystal. The calculation of CIE, CCT and intensity ratio of these glasses were shown reddish-orange emission.